Alte im Film und auf der Bühne: Neue Altersbilder und Altersrollen in den darstellenden Künsten - Hülsen-Esch, Andrea von; Herwig, Henriette (transcript, 2016)
Age reframed – film and theater discover age anew. This volume takes a multifaceted look at the medial staging of age and new images of age in all their complexity.